Effect of dislocation density distribution in work-hardened layer on cutting characteristics in the multi-cutting of 49Fe49Co2V alloy. (6th January 2023) - Zhang, Yuan; Kang, Renke; Dong, Zhigang; Bao, Yan; Guo, Dongming; Bai, Qian
Abstract: In the multi-cutting of metallic materials, the machined surface modification generated in the preceding cutting process, could further influence the cutting characteristic in the subsequent cutting. This paper investigates the effect of the work-hardened layer (WHL) on the subsequent cutting characteristics in the multi-cutting process of 49Fe49Co2V alloy. Firstly, the WHL features in terms of dislocation density, micro-hardness, and plastic deformation in the subsurface are studied experimentally. A modified Johnson-Cook (MJC) constitutive model with the consideration of dislocation density is developed to describe the dynamic behavior for the WHL. The FE model of an orthogonal cutting process is developed with the implementation of MJC model. In this model, the preceding cutting-induced dislocation density distribution is defined in the WHL. The cutting force is measured experimentally and used to verify the FE model. The cutting force, cutting temperature and stress distribution for the WHL and the bulk material are compared. It is found that in the multi-cutting with small cutting depths, the effect of dislocation density distribution in WHL on the cutting characteristics should be taken into consideration. The study could provide guidance to determination of the machining parameters in the multi-cutting.